A new species of Phasmatocoris from French Guiana, with short taxonomic notes on two described species and an updated key (Hemiptera: Heteroptera: Reduviidae: Emesinae) - Gil-Santana, Hélcio R. (Zootaxa, 2018)
Phasmatocoris papei sp. nov. (Hemiptera: Heteroptera: Reduviidae: Emesinae: Emesini) is described from French Guiana based on two male specimens. Short taxonomical notes on Phasmatocoris praecellens (Bergroth, 1911) and Ph. spectrum Breddin, 1904 are provided. An updated key to the species of Phasmatocoris Breddin, 1904 is presented.